Postmortems of Fatal Long Standing Hospital Admitted Cases, an Overburden for the Medico Legal Experts: A View - B.H. Tirpude; P.N. Murkey; Pawan A. Wankhade (Al Ameen Medical College, 2012)
Background: India is emerging as the most populated country of the world. Amount of Medico legal postmortems done in India are comparatively huge. On the contrarary, we have great deficiency of Forensic Experts and resources for conducting autopsy procedures. Owing to this disparity quality of Postmortem examination and other important medico legal work is not up to the mark. This is very much affecting the evidence collection solely on which decisions of our Judiciary system are based and many times it leads to miscarriage of Justice. Objectives: In Foreign countries Law, order and Forensic investigations are unfailingly of high standards and autopsies are performed only when highly recommended and demanded by the law enforcing agencies. Moreover restricted autopsies, minimal invasive autopsies etc are also performed there. Conclusion: Time has come to think and act over this issue for sake of Justice, Humanity and ultimately to save time, money and resources of Government agencies and for safety of working Forensic Experts those are at always stake.